On Faster Convergent Infinite Series - Dušan Holý; Ladislav Matejíčka; Ľudovít Pinda (International Journal of Mathematics and Mathematical Sciences, 2008)
Suffcient conditions, necessary conditions for faster convergent infinite series, faster 𝜏-convergent infinite series are studied. The faster convergence of infinite series of Kummer's type is proved.